A Convergent Strategy for the Synthesis of Second‐Generation Iminosugar Clusters Using "Clickable" Trivalent Dendrons. Issue 9 (23rd January 2014) - Joosten, Antoine; Schneider, Jérémy P.; Lepage, Mathieu L.; Tarnus, Céline; Bodlenner, Anne; Compain, Philippe
Abstract: A convergent strategy to access high‐valency iminosugar clusters based on two successive Cu I ‐catalysed azide–alkyne cycloadditions is reported. The key step of this approach relies on the grafting of azide‐armed trivalent iminosugar dendrons onto polyalkyne "clickable" scaffolds, thus tripling their initial valency. As a proof of concept, the synthesis of cyclodextrin‐based clusters containing the highest number of peripheral iminosugar ligands reported to date has been achieved. Evaluation of these compounds as mannosidase inhibitors revealed one of the strongest multivalent effects observed so far in glycosidase inhibition. Abstract : A convergent route to unprecedented neoglycoclusters containing up to 21 peripheral iminosugar ligands is reported. The synthetic strategy involves the grafting of azide‐armed trivalent dendrons onto polyalkyne "clickable" scaffolds by Cu I ‐catalysed azide–alkyne cycloadditions.